Quantitative detection of a1-acid glycoprotein (AGP) level in blood plasma using SERS and CNN transfer learning approach; Sensors and Actuators B: Chemical; Vol. 367 - Erzina M. Mariia; Trelin A.; Guselnikova O. A. Olga Andreevna; Skvortsova A.; Strnadova K.; Svorcik V.; Lyutakov O. Oleksy (2022, 2022)
Title screen